2005
DOI: 10.1080/13685530500137840
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and determinants of muscle strength change with aging in older men

Abstract: Decreased muscle strength with aging is associated with functional disability in older adults. However, few studies have longitudinally evaluated the rate of muscle strength loss and the risk factors for the loss in older men. This study examined the patterns and determinants of muscle strength change with aging in a healthy older male population. The study participants were 321 men (age range 51-84 yrs) recruited from population-based listings in the Pittsburgh region, USA. Grip strength was measured at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
32
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
10
32
2
2
Order By: Relevance
“…Height has been shown to correlate with muscle strength cross-sectionally among healthy young and older adults [22] . In our previous study of an elderly male population [23] , we observed that greater height loss since age 25 years was related to strength loss during 7 years of followup. Height change might act as an overall marker for long-term changes in body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Height has been shown to correlate with muscle strength cross-sectionally among healthy young and older adults [22] . In our previous study of an elderly male population [23] , we observed that greater height loss since age 25 years was related to strength loss during 7 years of followup. Height change might act as an overall marker for long-term changes in body composition.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, the development of sarcopenia is associated strongly with increased disability, gait and balance disorders, and mortality [6,7]. Muscle strength also declines with aging [8].…”
Section: Introductionmentioning
confidence: 99%
“…The age-related decline in grip strength in adults has been reported in a number of previous longitudinal studies 2,20,[36][37][38][39] . However, the trajectory of grip strength with aging has been described as linear 36,40,41) or curved/quadratic 37,42,43) , and some studies have illustrated the slope with flexion points.…”
Section: Grip Strength and Aging Processmentioning
confidence: 60%